Precedents and the role of analogy in Common Law and Islamic Law - Mohammad, Mohammad Tahir Sabit; Laluddin, Hayatullah (Serials Publications Pvt. Ltd., 2019)
This paper looks at the common grounds for legal reasoning based on analogy in common law and Islamic law. Despite the difference between the systems, based on the structure and sources, the use of judicial precedent and Qiyas (analogical reasoning) prima facie seem strikingly similar but unexplored. The authors look at the development stages of the two doctrines, the role of analogy, and the making of conclusions. The method of this doctrinal study is comparatively less synthetical and more analytical. The study finds that analogy does play a role in legal reasoning based on the doctrine of judicial precedent and Qiyas. However, there is a difference between the two doctrines where the analogy is the instrument of the discovery of facts in common law and of the discovery of rules and vice of them in Islamic law, which enable jurist to extend it to a new case that shares the vice of a previous case. Therefore, the certainty of rules and their uniformity seem stronger in Islamic law compared to common law.